2016
DOI: 10.3765/amp.v2i0.3750
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Phonotactics as Tier-Based Strictly 2-Local Languages

Abstract: This paper shows that the properties of locality observed for patterns of long-distance consonant agreement and disagreement belong to a well-defined and relatively simple class of subregular formal languages (stringsets) called the Tier-based Strictly 2-Local languages, and argues that analyzing them as such has desirable theoretical implications. Specifically, treating the two elements of a long-distance dependency as adjacent segments on the computationally defined notion of a tier allows for a unified acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…These findings are consistent with the hypothesis that the Tier-based Strictly 2-Local class of formal languages (TSL 2 ; delimits the range of learnable phonotactic patterns (McMullin, 2016;McMullin & Hansson, 2015;cf. Lai, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with the hypothesis that the Tier-based Strictly 2-Local class of formal languages (TSL 2 ; delimits the range of learnable phonotactic patterns (McMullin, 2016;McMullin & Hansson, 2015;cf. Lai, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…also Suzuki, 1998;Wayment, 2009). An alternative criterion, implicit in the term 'transvocalic' used here, is consonant-tier adjacency: Harmony applies if and only if no other consonant intervenes (Hansson, 2010;Jurgec, 2011;McMullin, 2016;McMullin & Hansson, 2015). Clear-cut evidence bearing on the choice between these interpretations is hard to come by (though consonant-tier adjacency seems slightly better supported; Hansson, 2010, pp.…”
Section: Locality Relations In Long-distance Phonotacticsmentioning
confidence: 99%
“…Heinz et al (2011) showed that long-distance phonotactics with blocking are Tier-based Strictly 2-Local. McMullin & Hansson argued that long-distance consonant agreement and disagreement are both Tier-based Strictly Local, and that transvocalic patterns are a special case of blocking (McMullin & Hansson 2016). Analogous to the fact that local phonotactic patterns can be characterized by Strictly Local languages, long-distance phonotactic patterns can be characterized by Strictly Piecewise (SP) languages (Heinz 2010).…”
Section: Future Workmentioning
confidence: 99%
“…Bennett 2015). Recent work in artificial grammar learning suggests that this crosslinguistic generalization is psychologically real: participants have a difficult time learning patterns in which a dissimilatory alternation occurs in less-local (and not more-local) contexts (McMullin & Hansson 2016). One way to formalize the notion that co-occurrence restrictions are sensitive to distance is to claim that co-occurrence constraints are gradiently evaluated (following Kimper 2011, Zymet 2015cf.…”
Section: The Typology Of Segmental Blockingmentioning
confidence: 99%
“…As noted by McMullin & Hansson (2016), the only known way to motivate context-free dissimilation in the SCTD is with the constraints in (40-41). With this modification, the SCTD is capable of accounting for the suffixal alternations as well as the root-internal restrictions present in the three cases documented here.…”
Section: 22mentioning
confidence: 99%